(untitled) (Bangladesh Journal of Medical Education, 2022)
‘Community-based medical education’ (CBME) consists of learning activities in the community settings where students, teachers and community members are actively engaged in the learning process of medical education relevant to community health needs. This cross sectional study was aimed to explore the current practices of CBME related activities in undergraduate medical education of Bangladesh. Data were collected from 108 teachers of eight medical colleges of Bangladesh from January to December of 2021 using a pretested self-administered questionnaire and analyzed by SPSS version 16. In this study, 61.1% were female teachers. Most of the teachers (69.4%) were agreed that CBME related activities motivate students to serve at community settings. About 74% teachers revealed that CBME develop student’s positive attitude towards community people. Maximum (51.9%) teachers were satisfied for infrastructure of residential field site training (RFST) sites. The accommodation, transport and security of RFST sites were satisfied to 38%, 45.4% and 47.2% teachers respectively. About 31.6% teachers mentioned that poor set up of service place for CBME activities and 23.7% teachers revealed that less participation of community people as important constraints for CBME related activities. Conduction of CBME related activities as per curriculum objectives and motivation of local health authority were most important suggestions to overcome the constraints of CBME related activities mentioned by 12.6% and 11.3% teachers respectively. This study recommended to motivate the stakeholders, increase duration for RFST, and ensure necessary infrastructures, adequate transport, security, resource and supervision for effective CBME related activities. Bangladesh Journal of Medical Education Vol.13(2) July 2022: 26-34